Peer-assisted learning: Perspectives of a former student tutor - Castelyn, Donovan (Australasian Tax Teachers Association, 2018)
Peer-Assisted Learning (‘PAL’) facilitates the reciprocal development of knowledge and skill between students of similar social groupings by disrupting the traditional student-teacher relationship. As an educational strategy, PAL strikes at the core of student collaboration, engagement and satisfaction. Given the ever-expanding digital landscape and advance towards online course delivery, PAL’s student-centered approach bridges gaps in course content delivery where conventional teaching practices would prove ineffective. PAL programs are equal parts flexible and adaptable to change, thus providing an attractive accompaniment to orthodox teaching methods. This paper will recollect on the author's experience as a PAL participant and facilitator. The paper will draw on key perspectives gained through these experiences and compare them with the prevailing literature on this topic. This paper will advocate for the use of the student tutor as additional resources to meet the needs of evolving student cohorts and to operate alongside traditional teaching practices. Conclusively, this paper will recommend to educators, particularly those teaching into the discipline of taxation in higher education, an implementation strategy to adopt and utilise PAL more effectively in the classroom and beyond.